The dissemination potential of Microsporidia MB in Anopheles arabiensis mosquitoes is modulated by temperature - Fidel Gabriel Otieno; Priscille Barreaux; Affognon Steeven Belvinos; Edward Edmond Makhulu; Thomas Ogao Onchuru; Anne Wambui Wairimu; Stancy Mandere Omboye; Cynthia Nyambura King’ori; Bonoukpoè Mawuko Sokame; Anthony Kebira Nyamache; Jeremy Keith Herren (Scientific Reports)
Abstract Microsporidia MB, a vertically transmitted endosymbiont of Anopheles mosquitoes, shows strong potential as a malaria control agent due to its ability to inhibit Plasmodium development within the mosquito host. To support its deployment in malaria transmission reduction strategies, it is critical to understand how environmental factors, particularly temperature, influence its infection dynamics. In this study, we investigated the impact of four temperature regimes (22 °C, 27 °C, 32 °C, and 37 °C) on Microsporidia MB prevalence and infection intensity by rearing mosquito larvae under controlled laboratory conditions. Our results demonstrate that elevated temperatures, especially 32 °C, significantly enhance both larval growth and Microsporidia MB infection rates. Population growth modeling further indicates that at 32 °C, an infected mosquito population can reach 1000 offspring within 15–35 days, representing a 4.7-, 1.3-, and 1.7-fold increase in dissemination potential compared to 22 °C, 27 °C, and 37 °C, respectively. Although mortality at 32 °C was approximately 20% higher than at 27 °C, this temperature emerged as the most favorable for mass-rearing Microsporidia MB-infected larvae. These findings provide the first insights into temperature-mediated dynamics of Microsporidia MB and support its potential for scalable implementation in malaria-endemic regions.